Sole Custody and The Implication of Fault-based Divorce Under the Indonesian Legal System - Hartini, Hartini; Ilhami, Haniah; Yusoff, Rahmawati Mohd (Journal of Indonesian Legal Studies, 2024)
This study analyses the reasons why most judges in Indonesia’s religious courts tend to rule in favour of the sole custody model over the joint custody model following a divorce, even though the state, through the Child Protection Act, has enacted regulations emphasizing the granting of child custody using the joint custody model. This study is an evaluative review of the dominant sole custody model decided in the Religious Court concerning the Indonesian divorce law system, which emphasizes that divorce must be filed for a reason. The study results show that the divorce law requiring divorce to be accompanied by a reason and adopted by the Religious Court makes Indonesia a country that adopts a fault-based divorce system. This impacts the contestation and efforts of one party to find fault with the other party through the proof process in the Religious Court. Furthermore, to show that one party is better and more moral, there is a struggle for child custody rights while affirming the presumption that the party winning child custody is the better and more moral party. This means that child custody is always given to one party, not to both parties. The Religious Court needs to consider the use of a no-fault divorce system for several reasons: (1) Islamic jurisprudence recognizes no-fault divorce, namely, divorce with khuluk (khul’), and (2) efforts not to defame the couple in court are more in line with Islamic teachings.